DETERMINANTS OF ACTUAL FINTECH USE IN MSMES: A MEDIATION EFFECT OF BEHAVIORAL INTENTION ON ATTITUDE AND ACTUAL USE - Dedy, Dedy; Sari, Maya; Salfarini, Eligia Monixa; Agustian, Aldy (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to determine the relationships among attitude toward use, behavioral intention to use, and actual use by utilizing the technology acceptance model. A quantitative research design was using multiple linear regressions. The study involved 90 samples from MSMEs in border areas selected through purposive sampling. The results indicate that attitude toward use significantly and positively affects actual use directly. Furthermore, behavioral intention to use also has a strong and significant effect on actual use. Behavioral intention to use as a mediator also gives a partial mediation between attitude toward use and actual use. These findings highlight that while positive attitudes can directly affect actual use, behavioral intention further enhances the likelihood of actual technology adoption. The study concludes that effective strategies to improve financial technology usage should simultaneously build positive attitudes and strengthen behavioral intention. Keywords: Attitude Toward Use; Behavior Intention To Use; Actual Use; Financial Technology